Antimicrobial activity of Yemeni myrrh mouthwash - Almekhlafi, Sadik; Thabit, Anes A. M.; Alwossabi, Ameen M. I.; Awadth, Nasser; Thabet, Abdulbaqi A. M.; Algaadari, Zaid (Journal of Chemical and Pharmaceutical Research, 2014)
This study aimed to prepare pharmaceutical formulations of mouthwashes, containing extracted Yemeni myrrh as a single active constituent, and testing their quality criteria and antimicrobial activity on common pathogens of the oral cavity. In order to determine the best extracting solvent for myrrh antimicrobial constituents, different solvents were used to prepare myrrh extract. The antimicrobial activity of those extracts against Staphylococcus aureus was then investigated. The extract that showed the best activity was also investigated against Streptococcus mutans and Candida albicans. It was found that the hydroalcohol extract extracted by ethanol: phosphate buffer pH 7 (85:15) showed the best antimicrobial activity. Thus, this extract was used, thereafter, to prepare 10 pharmaceutical formulations of myrrh tinctures. Each 100-ml tincture formulation was prepared from 65 ml of myrrh hydroalcohol extract (equivalent to 2.6 g extracted constituents of myrrh). All formulations contained a solubilizing agent, antioxidant, sweetener, flavor and colorant. In order to prepare corresponding aqueous myrrh mouthwash formulation form each tincture, 1ml of the tincture was diluted up to 50 ml with water. The viscosity, pH and palatability of those mouthwash formulations were tested. It was found that two formulations (M9, M10) prepared from the myrrh tinctures (F9 and F10, which contained 9.5 and 10.5 % w/v of sodium lauryl sulphate, respectively, showed accepted results. However, formulation M9 showed better antimicrobial activity than the other formulation. The antimicrobial activity of formulation M9 was also superior to those of two commercial mouthwashes and one oral antifungal suspension. Moreover, the formulation exhibited good isothermal short-term stability when stored at three different conditions for 9 weeks.